Association of adenosine signaling gene signature with estrogen receptor-positive breast and prostate cancer bone metastasis - Shropshire, Daniel Brian; Acosta, Francisca M.; Fang, Kun; Benavides, Jaime; Sun, Lu-Zhe; Jin, Victor X.; Jiang, Jean X. (Frontiers in Medicine, 2022)
Bone metastasis is a common and devastating consequence of several major cancer types, including breast and prostate. Osteocytes are the predominant bone cell, and through connexin (Cx) 43 hemichannels release ATP to the bone microenvironment that can be hydrolyzed to adenosine. Here, we investigated how genes related to ATP paracrine signaling are involved in two common bone-metastasizing malignancies, estrogen receptor positive (ER+) breast and prostate cancers. Compared to other sites, bone metastases of both cancer types expressed higher levels of ENTPD1 and NT5E, which encode CD39 and CD73, respectively, and hydrolyze ATP to adenosine. ADORA3, encoding the adenosine A3 receptor, had a similar expression pattern. In primary ER+ breast cancer, high levels of the triplet ENTPD1/NT5E/ADORA3 expression signature was correlated with lower overall, distant metastasis-free, and progression-free survival. In ER+ bone metastasis biopsies, this expression signature is associated with lower survival. This expression signature was also higher in bone-metastasizing primary prostate cancers than in those that caused other tumor events or did not lead to progressive disease. In 3D culture, a non-hydrolyzable ATP analog inhibited the growth of breast and prostate cancer cell lines more than ATP did. A3 inhibition also reduced spheroid growth. Large-scale screens by the Drug Repurposing Hub found ER+ breast cancer cell lines were uniquely sensitive to adenosine receptor antagonists. Together, these data suggest a vital role for extracellular ATP degradation and adenosine receptor signaling in cancer bone metastasis, and this study provides potential diagnostic means for bone metastasis and specific targets for treatment and prevention.